PERAN STRATEGIS LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN DALAM MEMBANGUN KARAKTER GURU PROFESIONAL - SYAFARUDDIN SYAFARUDDIN (Universitas Islam Negeri Sumatera Utara, 2016)
The role of produce educators education Institute (LPTK) in Indonesia is very strategic in setting up a professional teacher, both teachers of subjects as well as a classroom teacher at the school. A number of educational courses and practice field experience of contributing to the creation of the character of the candidates. Especially form the personal professional teacher candidate, in this case the competence of personality. The main character is honest, clean, respectful, caring, humble, confident, persistent, faithful, strong and high termanifestasikan taqwa in the everyday behavior of teachers is desirable in school and outside of school.